Status of Women Entrepreneurship in Uttarakhand: Exploring the Role of NGOs in Promoting Women Entrepreneurship in Uttarakhand (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Women set up their company for economic freedom and emancipation. This study aims to identify the factors promoting women entrepreneurship in the Indian state of Uttarakhand. While women growing become entrepreneurs, they do not have the right chance to pursue it. The role of non-governmental organizations (NGOs) in promoting the entrepreneurial cause of women is thus inevitable. The role of women and their place in any community is a measure of their civilization the contribution of women entrepreneurs to economic activities and jobs has grown over time. Women entrepreneurs created a number of innovative projects and helped grow a variety of facilities and products they are not only utilized but are often a justification for other jobs through showing work for them.